A Concise History of the Greek Catholic Church in Slovakia Following the Fall of the Communist Regime Historical and Social Excursus in the Years 1989 - 2002 - Coranic, Jaroslav (Communications - Scientific letters of the University of Zilina, 2017)
The purpose of this paper is to present a concise historical and wider societal development of the Greek Catholic Church in Slovakia, or more precisely in Czechoslovakia, in the years 1989 - 2002. The Velvet revolution of 1989 triggered a collapse of the totalitarian regime in Czechoslovakia, bringing positive changes for the Greek Catholic Church, too. 40 years of the Greek Catholic Church persecution in Slovakia had come to an end and the Church could finally seize the opportunity to fully rehabilitate and develop their activities in all spheres of life. In the years 1989 - 2002, the Church was led by the seventh Greek Catholic Bishop of Presov Mons. Jan Hirka, during which time numerous renewal processes started to take effect in the Church’s life.